Analisis Strategi Investasi Magic Formula pada Bursa Efek Indonesia - Jannah, Miftahul; Imansyah, Fadlul (Program Studi Akuntansi FPEB UPI, 2019)
Abstract. This study aims to investigate the performance of the magic formula investment strategy introduced by Joel Greenblatt (2006) which was applied to the Indonesia Stock Exchange. Magic formula is a simple stock selection strategy by ranking stocks based on return on capital and earnings yield. The next step is to choose the top thirty stocks from the combined rank to become a portfolio. The kompas100 index was chosen for the indonesia stock market. Returns from the magic formula portfolio are then compared to market returns. Portfolio rebalancing is conducted annually. Sharpe, treynor, and jensen’s alpha analysis is used to measure returns adjusted for risk. Overall, this study shows that using return on capital and earnings yields can produce higher average returns than the market index from april 2013 to april 2018. The magic formula portfolio yields an average return of 12.67% and the market produces average returns 5.31% during the period under test. Keywords. Earning Yield; Investment Strategy; Magic Formula; Return on Capital; Value Investing.Abstrak. Penelitian ini bertujuan untuk menyelidiki kinerja strategi investasi Magic Formula yang diperkenalkan oleh Joel Greenblatt (2006) yang diaplikasikan pada Bursa Efek Indonesia. Magic formula adalah strategi pemilihan saham sederhana dengan cara memeringkatkan saham berdasarkan return on capital dan earning yield. Langkah selanjutnya adalah memilih tiga puluh saham teratas dari peringkat gabungan untuk dijadikan portofolio. Indeks KOMPAS100 dipilih untuk pasar saham Indonesia. Pengembalian dari portofolio Magic Formula kemudian dibandingkan dengan pengembalian pasar. Rebalancing portofolio dilakukan tahunan. Analisis Sharpe, Treynor dan Jensen’s Alpha digunakan untuk mengukur pengembalian yang disesuaikan dengan risiko. Secara keseluruhan, penelitian ini menunjukkan bahwa dengan menggunakan return on capital dan earning yield mampu menghasilkan pengembalian rata-rata yang lebih tinggi daripada indeks pasar dari April 2013 sampai dengan April 2018. Portofolio Magic Formula menghasilkan pengembalian rata-rata 12.67% dan pasar menghasilkan pengembalian rata-rata 5.31% selama periode yang diuji. Kata kunci. Earning Yield; Strategi Investasi; Magic Formula; Return on Capital; Value Investing.